Pet photography 101 : tips for taking better photos of your cat or dog - Darlow, Andrew (Routledge, 2012)
Are you one of the 100 million people in the USA that own either a dog or a cat? If you flip through your digital camera - what do you see pictures of the most? Your kids ... and your pets! If you have ever wondered how to take pictures of an all black animal or how to get your pup to sit still during a family holiday picture, this book is for you. With love only a pet owner can have and humor that only animals can bring to us, this author shows how to take pictures that celebrate the furry creatures in our lives. Packed with techniques including lighting and postproduction and even info on getting those pictures up online, you'll be taking pictures of your pets that you'll be proud of.